"The ball is round, the game lasts 90 minutes, everything else is pure theory". (January 2021) - Jost, Peter-J.
We model a soccer match between two heterogeneous teams as a two-stage contest where each team chooses its attacking and defending effort for each half of the match. We characterize the optimal teams' efforts as well as the optimal effort allocation between offense and defense. In contrast to the theoretical literature on soccer we show, for example, that the leading team may preempt its competitor in the first half. Our analysis also sheds new light on empirical studies that investigate the change in winning points on the number of ties by showing that this effect depends crucially on teams' heterogeneity.